OP13 Immersive video for simulation debriefing: 'record and review' in 360-degrees using a virtual reality headset. (July 2019) - Nicholson, James; Gillespie, Ross; Bickerdike, Suzanne; Frith, Gareth; Hassan, Taj
Abstract : Aim: To introduce delegates to a simple, low-cost system of immersive 'record and review', using 360-degree video and a virtual reality headset to offer a new perspective during simulation debriefing. Objectives: Introduce a novel system of filming simulation in 360–degree video and immediate playback using a virtual reality headset. Share a methodology for evaluating 'immersivity' of video feedback by assessing participants' situational awareness. Compare learner experience (preference, usability, immersivity) between standard video and 360–degree video review. Advise delegates on key considerations to utilise 360–degree video debriefing in practice. Summary of work undertaken: The use of virtual reality (VR) in simulation training can provide an immersive and realistic learning experience. However, it remains the debriefing phase in which the most learning occurs. Video-based debriefing has been found to improve subsequent skill performance, compared to oral feedback alone 1 However, the use of 360-degree video in simulation debriefing has not yet been investigated. The authors developed a system to record simulation encounters using a 360-degree video camera and allow participants to immediately review the footage using a VR headset. Thirty-two medical students undertook a simulated resuscitation scenario and reviewed their performance using both VR and standard-video modalities. A comparison of situational awareness using each modality was performed by assessing participants' ability to identify critical steps performed or omitted. After using both modalities, participants completed a questionnaire to compare usability, immersivity and perceived educational benefit. Qualitative feedback sought to understand participants' experience of using VR as a debriefing tool. This is the first study to develop 'point-of-use' 360-video and virtual reality for simulation debriefing. Using the holistic TEL evaluation model, 2 the authors have completed the development phase and assessments of learner satisfaction and gain. Impact on practice: The key output of this study is the development of an easily reproducible system allowing the use of VR as a debriefing tool in simulation education. The participants in this study felt that VR provided a more immersive debriefing environment, in which they were more engaged in evaluating their performance and could get a clearer view of the events taking place. The authors hypothesise that 360-degree video allows participants to gain a better appreciation of their interactions with other individuals in the simulation. Simulation technologies have been shown to improve technical skill performance. 3 Immersive debriefing technologies may improve non-technical skill performance. By not relying on recall bias as a basis for debriefing, participants can observe the hidden influencers: the impact of cognitive biases, cognitive loading and communication on performance. This technology can now be trialled in practice by incorporating it into existing debriefing models and testing its usability with clinical educators. The authors hope that dissemination of this model will support those interested in immersive technologies to consider how they might utilise 360-degree video and virtual reality in their own courses. To help guide this, the presentation will also give advice on the cost of equipment, familiarisation of participants and how to choose effective camera angles. References: Spence AD, Derbyshire S, Walsh IK, Murray JM. Does video feedback analysis improve CPR performance in phase 5 medical students? BMC Med Educ 2016;16(1):203. Pickering JD, Joynes VC. A holistic model for evaluating the impact of individual technology-enhanced learning resources. Medical Teacher 2016;38(12):1242–1247, DOI: 10.1080/0142159X.2016.1210112 Cortegiani A, Russotto V, Montalto F, et al. Use of a Real-Time Training Software (Laerdal QCPR®) Compared to Instructor-Based Feedback for High-Quality Chest Compressions Acquisition in Secondary School Students: A Randomized Trial. PLoS One 2017;5(12):e0169591.